Peningkatkan Minat Dan Keterampilan Siswa Dalam Memahami Isi Teks Dengan Media Gambar Seri Dan Metode Diskusi Pelajaran Bahasa Indonesia - ., Windi Soleha; ., Ludfi Arya Wardana; ., Ryzca Siti Qomariyah (CV. ITTC INDONESIA, 2023)
Lessons in Indonesian continue to be given at every level of education, starting from elementary education to tertiary institutions with the aim of improving students' ability to communicate orally and in writing using Indonesian. However, there is a problem. This research was conducted because of the low interest and learning skills of students in learning Indonesian in class II MI Miftahul Huda Jrebeng Kidul Wonoasih. This is due to the incompatibility of the learning methods and media used in the discussion of understanding the contents of the text. For this reason, the researcher is interested in correcting this problem by utilizing the discussion method and picture series media. This research was carried out using the PTK method and the data analysis was descriptive qualitative by describing the research strategy realistically based on the data obtained. The results obtained after the research showed an increase in the average interest with an average pre-cycle of 38, an average of 47 in the first cycle and an average of 79 in the second cycle. cycle I and 80 in cycle II.